The relationship between in-vitro endothelial permeability and molecules of the intercellular junction - Budworth, Rachel Ann (2003)
Changes in endothelial permeability are known to contribute to many pathologies, including inflammation seen in skin irritation. The regulation of permeability has been linked to inter-endothelial junctions, specifically the tight and adherens junctions (TJ and AJ). The functional state of the junction is thought to be associated with numerous factors including cytoskeletal changes and the interactions between junctional components. How these factors interact and respond to inflammatory stimuli is still not fully understood.